Integrasi Sejarah Lokal Melalui Media Youtube dalam Meningkatkan Kemampuan Berpikir Kritis pada Mata Pelajaran Sejarah Kelas XI SMA Negeri 5 Kota Madiun - Pratama, Setya Yoga; Hartono, Yudi; Nurkholipah, Siti (LPPM Universitas Putera Batam, 2024)
Taufik Abdullah's statement regarding the weakness of the pedagogical strategy of Indonesian history can still be found today. However, the Merdeka curriculum provides a glimmer of hope for history teachers in creating more interesting and meaningful history learning. This novelty can be used to insert local-based knowledge into students. For history teachers, this can be done by integrating local history into learning materials. Integration of local history can be a way out of the problem of weak history education strategies at the school level. This article aims to analyze the effectiveness of using YouTube as a medium in integrating local history into history subjects to improve students' critical thinking skills. The method used is the Kemmis and McTaggart model of classroom action research carried out in two cycles. Furthermore, this study uses a qualitative approach with data collection techniques in the form of observation and written tests. The results of this study indicate that the use of YouTube as a learning medium equipped with the integration of local history can improve students' critical thinking skills. This can be seen from the increase in the quality of analysis, understanding of the material, discussions, and answers given when the test is given. The success of this research is also inseparable from the influence of several factors such as (1) the relevance between the discussion theme and the background of the students; (2) the needs of the students; (3) the availability of learning materials; and (4) the use of digital media as part of learning activities.